Pseudo-pseudo-hypoparathyroidism with coarctation of the aorta—a clinical syndrome? - de Swiet, J. (1973)
Two cases of pseudo-pseudo-hypoparathyroidism are described, associated with coarctation of the aorta, suggesting a further common clinical link (besides those already recognized) between the former condition and Turner's syndrome. The need for a change of nomenclature of pseudo-pseudo-hypoparathyroidism is emphasized.